The press effect : politicians, journalists, and the stories that shape the political world - Jamieson, Kathleen Hall (Oxford University Press, 2002)
Was the 2000 US presidential campaign merely a contest between Pinocchio and Dumbo? And did Dumbo miraculously transform after September 11? The authors argue that these types of stereotypes represent the failure of the press and citizenry to engage with the political process in a critical fashion.